PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAPPEMBATALAN TRANSAKSI ONLINE SECARA SEPIHAKOLEH PIHAK TOKOPEDIA - Salma Salsabila, (2022)
As technology develops, more and more economic activities are carried out via the internet. For example in the trade sector where many people rely on ecommerce as a medium of buying and selling. E-Commerce is a gathering place for sellers and buyers on a website. Tokopedia is one of the most well-known ecommerce sites in Indonesia. However, the existence of e-commerce does not rule out the possibility of losses borne by consumers due to errors from business actors. As is the case with the cancellation of transactions made unilaterally by Tokopedia. Based on the legal facts that have been described, it can be concluded that Tokopedia cannot cancel online transactions unilaterally to consumers because the action is contrary to violating Article 11, Article 12, Article 16 and Article 18 of Law Number 8 of 1999 concerning Consumer Protection. This research is a normative juridical research by taking primary, secondary, and tertiary data sources. Legal protection for consumers who suffer losses due to the cancellation of transactions made unilaterally by Tokopedia has not been specifically regulated, but in the Consumer Protection Act. Consumers who experience losses due to the cancellation of transactions made unilaterally by Tokopedia can take settlement efforts using litigation or non-litigation channels. Such as complaining against the Indonesian Consumers Foundation (YLKI) or the Consumer Dispute Resolution Agency (BPSK). Key Word : Unilateral Cancellation, E-Commerce Transaction, Tokopedia